2022
DOI: 10.1186/s12888-022-04472-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring risk factors for re-hospitalization in a psychiatric inpatient setting: a retrospective naturalistic study

Abstract: Background The reduction of multiple psychiatric hospitalizations is an important clinical challenge in mental health care. In fact, psychiatric re-hospitalization negatively affects the quality of life and the life expectancy of patients with psychiatric disorders. For these reasons, identifying predictors of re-hospitalization is important for better managing psychiatric patients. The first purpose of the present study was to examine the readmission rate in a large sample of inpatients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…However, the literature shows conflicting results. Some studies also confirm this risk factor, which has previously been identified in studies conducted in inpatient settings (18,24); in other studies, this risk factor was unclear, with nonsignificant results (11,21,25). The ability to have a job, which has been collected in our study with the variable "unskilled worker", has been identified as a protective factor in the multivariable logistic regression model (p-value: 0.006) adjusted for potential confounders, as illustrated in Table 2: aOR of 0.26 (95% CI: 0.10-0.65).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, the literature shows conflicting results. Some studies also confirm this risk factor, which has previously been identified in studies conducted in inpatient settings (18,24); in other studies, this risk factor was unclear, with nonsignificant results (11,21,25). The ability to have a job, which has been collected in our study with the variable "unskilled worker", has been identified as a protective factor in the multivariable logistic regression model (p-value: 0.006) adjusted for potential confounders, as illustrated in Table 2: aOR of 0.26 (95% CI: 0.10-0.65).…”
Section: Discussionsupporting
confidence: 66%
“…This risk factor has already been identified, particularly in schizophrenic patients ( 23 ). In another study, conducted without distinction of psychiatric pathology and still in an inpatient setting, no statistical association was found ( 18 ). Medical follow-up discontinuation in psychiatry has also already been studied in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Competing risk regression analyses based on Fine and Gray’s proportional subhazards model were used to identify predictors of psychiatric hospitalisation (with reincarceration as a competing event) 14. Potential confounding variables were selected a priori for inclusion in the regression analyses based on literature review of prior research 8 9 15–17. The following variables were included in the univariate analysis: sex, age at baseline, Indigenous status, index supervision status, parental incarceration, parental death, out-of-home care placement, previous incarceration, head injury, substance use disorder, psychosis, mood and anxiety disorder, personality disorder, behavioural disorder and intellectual and neurodevelopmental disorder.…”
Section: Methodsmentioning
confidence: 99%